# Alternate proof for weighted alternating shifted central binomial sum relation

In two recent posts, MSE 2824529 and MSE 2825442, both initiated by user196574, I answered two asymptotic questions for $$n \to \infty$$ with the following identity:

$$\,\,\,\,\,\sum_{k=1}^n (-1)^{k+1} \binom{2n}{n+k} k^s = \binom{2n}{n} \sin(\pi s/2) \int_0^\infty \frac{dx \, \,x^s}{\sinh{\pi x}} \frac{n!^2}{(n+ix)!(n-ix)!}.$$

I'm asking for a simpler proof or a generalization in which this formula is a special case. For scoring, Generalization > Simplicity.

An example of a generalization might be a Dirichlet character analog. So on the left there is squeezed in some sequence of (+1,-1,0) and on the RHS the hyperbolic trig function might get replaced with something more complicated, like a ratio of a linear combination of hyperbolic trig functions.

My proof, as requested from two contributors, will follow.

I was also asked for the motivation for such a formula. It wasn't for asymptotics, but instead to cobble a proof of the functional equation for Riemann's zeta function (at least formally) by using a hypergeometric identity. Since there are many rigorous proofs for the functional equation (and I don't publish anyway) I'd almost forgotten about it. If someone can generalize the formula as suggested above, it may be worth a revisit.

$$\textbf{Proof}$$

Establish the formula, valid for $$0 < Re\,s < 2n$$ $$\,\,\,\,\,\sum_{k=1}^n (-1)^{k+1} \binom{2n}{n+k} k^s = 2^{2n-s}\frac{s!}{\pi}\, \sin(\pi s/2) \int_0^\infty \frac{dt}{t^{s+1}}\, \sin^{2n}t.$$ The next few lines reproduce a well-known trig ID. By the binomial theorem $$\sum_{k=0}^{2n}\binom{2n}{k}(-x)^k = (x-1)^{2n}=\sum_{k=-n}^n\binom{2n}{k+n}(-x)^{k+n}$$ By splitting the sum at $$k=-1$$ and $$k=1$$ we have $$\sum_{k=1}^n (-1)^k\binom{2n}{n+k}\big(x^k + x^{-k} \big) = (-1)^n(x-1)^{2n}\,x^{-n} - \binom{2n}{n}.$$ Insert $$x=\exp{(2it)}$$ to get $$\,\,\,\,\,(2\sin t)^{2n}= 2\sum_{k=1}^n (-1)^k\binom{2n}{n+k}\cos(2\, k\, t) + \binom{2n}{n}.$$ Insert Left Hand Side (LHS) of previous equation into integral on RHS of eq . Also insert a regularizer $$\exp{(-p\,t)}$$ and we'll let $$p \to 0$$:

$$\int_0^\infty \frac{(2\sin{t})^{2n}}{t^{s+1}}dt = \lim_{p\to 0} \int_0^\infty dt \Big(2\sum_{k=1}^n (-1)^k\binom{2n}{n+k}\cos(2\, k\, t) + \binom{2n}{n} \Big)\frac{e^{-pt}}{t^{s+1}}.$$ $$= \lim_{p\to 0} 2\sum_{k=1}^n (-1)^k\binom{2n}{n+k}\Gamma(-s)\cos\big(s \arctan(2k/p)\big)(p^2+(2k)^2)^{s/2} + \binom{2n}{n}\Gamma(-s)p^{s}$$ where the Euler integral for the $$\Gamma$$ function has been used. The requirement $$s>0$$ and the assumption $$s$$ not an integer will mean the last term $$\to$$ 0. The last assumption will be relaxed upon analytic continuation. Taking the limit, e.g. $$lim_{p\to 0} \arctan(2k/p)=\pi/2$$ and using the reflection formula for the $$\Gamma$$ function allows us to write the result as eq . Analytic continuation permits the $$s$$ to be extended to the stated range. The proof of  is complete.

Now the $$t^{-s-1}$$ will be represented by the Euler integral to derive a double integral that will eventually give rise to the form in eq. . $$s!\int_0^\infty \sin^{2n}\!t\frac{dt}{t^{s+1}}= \int_0^\infty dt \sin^{2n}t\int_0^\infty\exp{(-xt)}x^s dx = \int_0^\infty dx \, x^s \int_0^\infty dt\, e^{-xt}\sin^{2n}\!t$$

Now we'll show $$\,\,\,\, J := \int_0^\infty dt\, e^{-xt}\big(2\,\sin{t}\big)^{2n} = (2n)! \frac{i}{2} \frac{\Gamma(ix/2)}{(n+ix/2)!} \frac{\Gamma(1-ix/2)}{(n-ix/2)!}$$ Again insert  into the LHS of 4, and again use the Euler integral to find $$J=2\sum_{k=1}^n (-1)^k\binom{2n}{n+k}\frac{x}{x^2+(2k)^2} + \binom{2n}{n}\frac{1}{x}$$ $$=\binom{2n}{n}\Big( 2\sum_{k=1}^n\frac{(-n)_k}{(n+1)_k}\frac{x}{x^2+(2k)^2} + \frac{1}{x} \Big)$$ where the expression in the last line uses the Pochhammer symbol. Now the following identity is known, e.g.,Table of Series and Products, Hansen 6.6.57: $$\sum_{k=1}^n \frac{(-n)_k}{(n+1)_k}\frac{1}{k^2-a^2} = \frac{1}{2a^2} \Big(1-\frac{n!^2}{(1+a)_n\,(1-a)_n} \Big).$$ Use of it completes the proof of . Use the $$\Gamma$$ reflection formula, rescale the integral and do some algebra and the proof of eq.  is complete.

• Integrating (modulo prefactors) $$f(z)=\frac{z^s}{\sinh(\pi z)}\frac{1}{\Gamma(n+i z+1)\Gamma(n-i z+1)}$$ around a keyhole contour in the complex plane proofs this result pretty fast Jun 22, 2018 at 15:24

Sorry to bump an old question, but I thought this would interest you.

In this paper with Divesh Aggarwal, Huck Bennett, and Sasha Golovnev, we ended up using this identity and a generalization of it to prove certain computational hardness results for lattice problems. See Section 7 there.

Here's the full statement: OP's statement corresponds to the case when $$k = 2\tau$$.

The proof uses the contour integration idea suggested by @tired.

Anyway, thanks for posting this! I doubt we would have discovered this identity without you!

• Thank you for including a call out in your paper. It really means a lot to me since I don't get to do that kind of research. Your generalization is very good, too. In another problem I asked for a different kind of generalization, b/c with formula  I was able to prove the function equation of the Riemann zeta function. May 4, 2020 at 3:30